Flow characteristics and intrinsic workability of IN718 superalloy - Chen, Fei; Liu, Juan; Ou, Hengan; Lu, Bin; Cui, Zhenshan; Long, Hui (Elsevier, 2015)
This study focuses on deformation characteristics of superalloy IN718 by formulation of a new flowstress model and detailed evaluation of intrinsic workability through the generation of three-dimensional (3D) processing maps with the support of optical microstructural observations. Based on thermomechanical simulation tests using a Gleeble-1500 machine, the flow stress model for superalloy IN718 was built and the flow stress throughout the entire deformation process was described by a peak stress only depending on Zener–Hollomon parameter and strain. The developed model exhibited the strain softening due to dynamic recrystallization (DRX). The intrinsic workability was further investigated by constructing 3D processing maps. The 3D processing maps described the variations of the efficiency of power dissipation and flow instability domains as a function of strain rate, temperature and strain, from which the favourite deformation conditions for thermomechanical processing of IN718 can be established.